E-działania w obszarze wsparcia przewozu pasażerskiego na przykładzie Szybkiej Kolei Miejskiej w Warszawie .......... 347 - Beroud, Alan (E-administracja: Wyzwania dla cyfrowych usług publicznych w Unii Europejskiej, 2024)
E-ACTIVITIES IN THE AREA OF PASSENGER TRANSPORT ASSISTANCE ON THE EXAMPLE OF THE RAPID URBAN RAIL IN WARSAWThe paper addresses the most important, key issues related to passenger transport as part of both broadly and narrowly defined urban transport. The author took up the challenge in the form of an approximation of the characteristics of passenger transport in the capital city of Warsaw on the example of the Rapid Urban Rail. In particular, he referred to the issues related to the growing importance of e-services as part of the offer formulated for the passenger by the carrier. It also outlines prospects for the development of passenger transport on the example of the Rapid Urban Rail in Warsaw.